Reintegrasi Sains dan Agama: Kajian Aksiologi Mekanika Newtonian dan Signifikansinya Terhadap Pendidikan Karakter Siswa - Miladanta, Algi Nurahman; Irawan, Irawan; Hasanah, Aan (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – This research aims to reveal the significance of one of the scientific theories, namely Newtonian mechanics, which is viewed from the philosophical-axiological aspect of student character education in the context of the reintegration of science and religion. So, a test was carried out on MTs Darul Fikri students in building a character education environment at school.Methods – This research design uses discussion group methods, interviews, observation, and documentation as instruments for researchers to collect data in the field. The research method was carried out using a descriptive-qualitative approach to obtain information regarding learning in schools, curriculum, approaches, strategies, methods, and learning models used, as well as data regarding the cognitive and affective aspects of students in the field.Findings – The research findings show that scientific concepts such as Newtonian mechanics can be integrated with religious values in the context of student character education. These findings support the idea that integration between science and religion can have a positive impact on the formation of students' character.Research Implications – The implication is that character education that includes moral values and the usefulness of science can be instilled through scientific concepts such as Newtonian mechanics. The limitations of this research are that there has been no concrete implementation of the integration of science and religion in the character education curriculum, and there has been no development of learning methods that effectively combine scientific concepts and religious values.